2006
DOI: 10.1093/rfs/hhj032
|View full text |Cite
|
Sign up to set email alerts
|

Investor Overconfidence and Trading Volume

Abstract: and the PACAP/FMA and EFA conferences. Meir Statman acknowledges support from the Dean Witter Foundation. We thank Greg Adams for database support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
325
5
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 768 publications
(364 citation statements)
references
References 59 publications
33
325
5
1
Order By: Relevance
“…Market-wide panel VAR model is used as econometric technique to check the relationship between return and turnover (Statman et al, 2006). VAR results indicated that historical market return is negatively related with turnover which is strong indication of overconfidence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Market-wide panel VAR model is used as econometric technique to check the relationship between return and turnover (Statman et al, 2006). VAR results indicated that historical market return is negatively related with turnover which is strong indication of overconfidence.…”
Section: Resultsmentioning
confidence: 99%
“…So investor overconfidence is one factor which leads to excessive trading. For example, Statman, Thorley, and Vorkink (2006) concluded that turnovers and lag returns predict future returns and this was found in trading levels. Overconfident investors often experience significant losses and expenses (Odean, 1998).…”
Section: Public Interest Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…8, No. 10;2016 With regard to the market trend variables, recently rising and falling markets, it is expected that market liquidity will increase following the increase in the past market moves and vice versa, which may be due to the contrarian, momentum or overconfidence theories (see, e.g., Chordia et al, 2001;Gervais & Odean, 2001;Statman et al, 2006;Glaser & Weber, 2009). However, our results provide inconclusive evidence.…”
Section: Ijefccsenetorgmentioning
confidence: 99%